Stock Market Overreaction and Trading Volume: Evidence from Malaysia - Ruhani Ali; Zamri Ahmad; Shangkari V. Anusakumar (Asian Academy of Management Journal of Accounting and Finance, 2011)
We investigate the stock market overreaction in Bursa Malaysia from January 2000 to October 2010 using weekly data. We find that winner portfolios tend to have negative returns whereas loser portfolios have positive returns for various holding periods from 1 to 52 weeks. Loser stocks experience more persistent and stronger return reversals than winner stocks. The evidence implies that a lower level of overreaction exists for winner stocks. Overall, a loser-winner portfolio yields highly significant returns. Comparing the overreaction of low-, medium- and high-volume stocks, we find that low volume stocks experience more consistent and larger return reversals. Therefore, trading volume is inversely related to overreaction. We also document more persistent overreaction for loser than winner stocks for all volume categories. In addition to contributing to the literature on stock market overreaction, our findings also have practical implications for investors.